2012
DOI: 10.3892/mmr.2012.1252
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and spectrum of GJA5 mutations associated with lone atrial fibrillation

Abstract: Abstract. Atrial fibrillation (AF) is the most common form of cardiac arrhythmia observed in clinical practice and a major contributor to cardiovascular morbidity and mortality. Accumulating evidence indicates a substantial genetic basis for AF. However, AF is genetically heterogeneous and the hereditary components responsible for AF remain to be identified in the majority of patients. The cardiac gap junction protein α 5 (GJA5) is specifically expressed in atrial myocytes and is associated with the coordinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 60 publications
0
15
0
1
Order By: Relevance
“…AF, the most common form of sustained cardiac arrhythmia, is characterized by uncoordinated atrial activation and chaotic electrical activity, with consequent deterioration of atrial mechanical function (19). Using the in vitro rat AMC culture and rapid pacing model, the present study demonstrated that rapid pacing shortened the APD and downregulated the expression levels of LTCC and potassium channels.…”
Section: Discussionmentioning
confidence: 51%
“…AF, the most common form of sustained cardiac arrhythmia, is characterized by uncoordinated atrial activation and chaotic electrical activity, with consequent deterioration of atrial mechanical function (19). Using the in vitro rat AMC culture and rapid pacing model, the present study demonstrated that rapid pacing shortened the APD and downregulated the expression levels of LTCC and potassium channels.…”
Section: Discussionmentioning
confidence: 51%
“…Both somatic and germ-line mutations of Cx40 have been identified in patients with lone AF [1416, 29]. These mutations apparently contribute to AF by reducing the abundance of functional Cx40.…”
Section: Discussionmentioning
confidence: 99%
“…that are crucial for cardiovascular development, including ANF and CX40 (27,(38)(39)(40)(41). In addition, loss-of-function mutations in several transcriptionally cooperative partners and target molecules of TBX5, including NKX2-5, GATA4, GATA5, GATA6, ANF and CX40, have been implicated in the pathogenesis of AF in humans (8)(9)(10)(11)(12)(13)(14)(42)(43)(44). Therefore, functionally impaired TBX5 may contribute to AF by reducing the expression of target genes.…”
Section: A B Cmentioning
confidence: 99%